If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+(-x+1)=1
We move all terms to the left:
x+(-x+1)-(1)=0
We add all the numbers together, and all the variables
x+(-1x+1)-1=0
We get rid of parentheses
x-1x+1-1=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| (x+133)=180 | | -9.2(x-2.75)=18.4 | | X2+y2+10=10y | | -2v/7=-4 | | -6m+5=-25 | | x+3x4x3=90 | | .5(4x)=140 | | 12-4x=x2+42x+441 | | 8x=57-x+3 | | x-1000=560 | | 4e^2+2e^2=150 | | -8(2x+5)+24x=96+8x | | -13+n/2=-11 | | 9x+45=18x | | x+52+52=360 | | 4x+13+5x-12=180 | | 2(w-4)+5w=20 | | 3^x+3^x+1=325 | | 0=9a-a | | 3+x=-3x+6+4x | | 3^x+3x+1=325 | | 190+10+y=360 | | -8(6a+8)+6=230 | | x-10+x-10=360 | | -8+4x=3x-12 | | 9=2g+g | | -7(5x-7)=-196 | | -3x+9=6-4x | | 9(q-2)=3(q-2) | | 7(8r-7)-2=397 | | 25-(-8+9(x+3)=0 | | 2x+2x/4=180 |